New species of Staphylinidae (Coleoptera) from Republic of Moldova (One Health & Risk Management, 2024)
Introduction. Saproxylic beetles are important components of biodiversity and are used for monitoring the quality of old-growth forests. Due to the substantial reduction of forested areas and low availability of dead wood, saproxylic beetles are becoming threatened and many small coleopteran species risk disappearing before they are even discovered.Material and methods. The research was carried out in one natural forest, three natural and two landscape reserves. Coleoptera species were identified using morphological characters and DNA barcoding. Molecular identification established using the GenBank database were confirmed by querying the BOLD Systems database.Results. The work includes 9 species of coleoptera: Batrisodes unisexualis, Trichonyx sulcicollis, Sepedophilus bipunctatus, S. constans, S. pedicularius, Gyrophaena manca, Scaphisoma agaricinum, Medon rufiventris and Hypnogyra angularis newly identified for the fauna of the Republic of Moldova. Obtained COI sequences were analysed and compared with European  species stored in GenBank. From a phytogeographic point of view, the majority of the sequences from the Republic of Moldova are grouped into private haplotypes, that are distributed only in the analysed region. The species Gyrophaena manca has 2 haplotypes, one is present in Finland and Germany, another in the Republic of Moldova.Conclusions. As a result of the research 9 species of saproxylic coleoptera from the studied natural forests were identified as new for the fauna of the Republic of Moldova.  Obtained genetic data are available for future phylogeny, phylogeography and conservation biology studies carried out at European level.